Operational and production determinants contributing towards commercialization among female Agripreneurs in Vhembe district - Tshikororo, Mpho; Khorombi, Takalani Isaac (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigates operational and production determinants that significantly influence small-scale transitioning to commercial farming among female agripreneurs, the implications for food security and gender equality with various elements impacting the commercialization of agricultural production in emerging economies. A quantitative research design was used in this research. This study was conducted in the emerging economic zone, the Vhembe district of Limpopo province where agricultural activities dominate. A purposive sampling was used to select 149 female agripreneurs. Structured questionnaires were handed to the participants during the in-person interview sessions. The study results reveal that the sample was dominated by elderly agripreneurs who primarily relied on permission to occupy arrangements for land security. The study findings exhibit that operation determinants such as type of farming and record keeping were positive contributors towards commercialization among female agripreneurs. Meanwhile, production elements such as commodity types regressed the commercialization effort among female agripreneurs. The study findings imply that policy tools should advocate for land security among female agripreneurs as they enhance the implementation of their long-term agricultural plans. The study findings suggest that emerging female agripreneurs should be made aware of various farming types that propel commercialization within a shorter period due to their lifecycle.